Extração de ácidos graxos produzidos por Mortierella isabellina utilizando fluido supercrítico e ultrassom - Sallet, Daniela (2017)
Polyunsaturated fatty acids (PUFA) have received considerable attention in recent years due to the benefits associated with their consumption. Among these benefits, they emphasize their multiple physiological actions, playing a crucial role in human metabolism, as well as maintaining a healthy state, being also associated with the decrease of some factors related to cardiovascular disease. The production of PUFA in fermentative processes is intracellular and an efficient extraction process of these fatty acids is necessary for its commercialization. Therefore, the main objective of this work was to define a methodology for the extraction of PUFA produced by submerged fermentation from the fungus Mortierella isabellina through supercritical fluid and ultrasound. Two methods of extraction were studied: supercritical fluid extraction (SFE) and ultrasonic assisted extraction. In supercritical extraction were used supercritical carbon dioxide (SFE-CO2) and compressed liquefied petroleum gas (LPG). In the extraction with SFE-CO2 the pressure varied in the range of 150 to 250 bar and the temperature between 40 to 80 ºC, already for the extraction with compressed LPG, the pressure and the temperature were in the range of 10 to 20 bar and 20 to 40 ºC, respectively, extraction yield, the kinetic parameters and the fatty acid profile were evaluated. According to the kinetic curves, mass transfer rates, and extract yields, 80 °C / 250 bar (SFE-CO2) and 40 °C / 20 bar (LPG) were the most favorable conditions for the extraction of lipids from biomass, in these conditions, the yields were 3.21 and 4.45%, respectively. According to the fatty acid profile, the SFE-CO2 provided a slightly higher performance than the compressed LPG. In the ultrasonic assisted extraction two solvents were used: ethanol and a mixture of solvents composed of chloroform: methanol: water in ratios of 1:2:0.88. Ultrasound intensity (17-85 W.cm-2) and pulse cycle (0.5 - 1.0) were evaluated through an experimental design in extraction and fatty acids profile. In the best extraction condition, with an intensity of 75.11 W.cm-2 and the pulse factor of 0.93, the lipid yield was 14.47% using ethanol and 19.49% using the mixture of solvents. The main fatty acids identified were estearic (C18:0), cis-10-pentadecanoic (C15:1), cis-10-heptadecanoic (C17:1), oleic (C18:1n9c), arachidic (C20:0), linoleic (C18:2n6c), α-linolenic (C18:3n3) and palmitic (C16:0). The extraction with ultrasound using ethanol showed a better profile of fatty acids, and a higher concentration of PUFA. The main results confirmed that the ultrasonic assisted extraction is a promising methodology for obtaining fatty acids from microbial biomass.